Analysis of Employee Empowerment through Planning in Sukamakmur District, Bogor Regency - Ginung Pratidina; Abubakar Iskandar (International Journal of Social Sciences: Current and Future Research Trends, 2024)
Empowerment is an effort to improve employees whose performance is classified as low to become high performance. In this sense, when linked to planning, this effort is a Sukamakmur sub-district government program to optimize planning performance and performance accountability. Both of these things will significantly influence performance. The aim of this research is to describe the employee empowerment model; Analyze planning performance; Analyzing performance accountability. This research uses a "Phenomenology" perspective. Meanwhile, the method used is a survey. Therefore, the approach used is a conventional approach. The samples taken were 35 informants. The data taken is primary and secondary data. Data collection was carried out through method triangulation and source triangulation. Data analysis was carried out through performance planning and performance accountability. Research shows that the Employee Empowerment Model uses a "cognitive approach" and a "participatory approach." In addition, this approach allows leaders to evaluate planning performance and performance accountability. Performance planning includes several components, namely administrative services and employee training. Meanwhile, the level of implementation of planning is the basis for assessing the success and failure of implementing programs and activities according to the goals and objectives that have been set. Meanwhile, the level of reporting that is timely and on target is in accordance with the implementation of planning. Meanwhile, performance accountability consists of service quality and sub-district training. The quality of administrative services both quantitatively and qualitatively for employees in Sukamakmur District is in the "very high quality" category. Meanwhile, the level of sub-district training, both mental and spiritual training, performance development and discipline training and training in Sukamakmur Sub-district is in the "very successful" category.